(untitled) (Research, Society and Development, 2021)
This study, which aims to reflect on teaching strategies based on Universal Design for Learning (DUA) articulated the use of digital technologies, in the context of the COVID Pandemic 19. Thus, it aimed to understand how the training processes and practices developed in the model remote, carried out in the 2020 academic period, to know how academics analyzed the practices implemented and implemented by teachers and to identify elements that signal for practices based on DUA articulated to the use of digital technologies. The research, which privileged the qualitative approach, was developed in the scope of a state public University of the State of Paraná and classes of the fourth year of the pedagogy degree course participated and the subject was composed of seventeen students. Data collection took place in the months of June and July 2020 and as a tool, a questionnaire containing five open questions was used, which were answered via Google Docs. The subjects’ speeches were organized for analysis based on two themes, namely: remote teaching changes without changes: the limits experienced in practice and remote teaching and use of technologies: approximations with the principles of universal design for learning. It is concluded that technological resources and digital media assist the “being together” of the teacher with the student, helping their knowledge construction process and that digital media offer an immense range of possibilities, as long as they are linked to the principles of the DUA.